Evaluación psicológica en adicciones: caso clínico - Rivera Barreto, Jeannine Estefanía (My University, 2021)
The psychological evaluation and psychodiagnosis allows us to analyze the behavior of the human being by means of different tools that evaluate the different areas of the psychological functioning of the patient affective, cognitive and relational to collect information according to the clinical case of addictions among which the following were applied, the interview, observation and Assist test that allows us to identify the level of affectation of the consumption of psychotropic substances in the social, family and work areas. And the Hamilton anxiety test that allows analyzing the severity of anxiety. The psychodiagnosis also includes categories such as the motive system, attachment systems, locus of control, resilience, hope and self-efficacy, protective factors that reduce the possibility of a person entering the world of addictions by strengthening self-esteem, social skills and problem-solving capacity, strengthening the personality and reducing the development of excessive habit problems.
La evaluación psicológica y el psicodiagnóstico nos permite analizar el comportamiento del ser humano mediante diferentes herramientas que evalúa las diferentes áreas del funcionamiento psicológico del paciente afectiva, cognitiva y relacional para recabar la información de acuerdo al caso clínico de adiciones entre las cuales se aplicó, la entrevista, observación y test Assist que permite identificar el nivel de afectación del consumo de sustancias psicotrópicas en las áreas social, familiar y laboral. Y el test de ansiedad de Hamilton que permite analizar la severidad de la ansiedad. En el psicodiagnóstico además se incluyen categorías como, el sistema de motivos, sistemas de apego, locus de control, resiliencia, esperanza y autoeficacia, factores protectores que disminuyen la posibilidad de que una persona ingrese al mundo de las adicciones fortaleciendo la autoestima, las habilidades sociales y la capacidad de resolución de problemas, fortaleciendo la personalidad y reduciendo el desarrollo de problemas de hábitos excesivos.
Keywords: EVALUACION PSICOLOGICA; PSICODIAGNOSTICO; ADICCION; FACTOR PROTECTOR